ANALYSIS OF SUITABILITY AND CARRYING CAPACITY OF SAMUDRA INDAH BEACH TOURISM AREAS IN SUNGAI RAYA KEPULAUAN SUBDISTRICT BENGKAYANG DISTRICT - HARIYANTO, BAMBANG; inpurwanto, inpurwanto; hurriyani, yeni (Jurnal Sains Mahasiswa Pertanian, 2020)
Samudra Indah Beach is one of the developing tourism areas. The development of marine tourism areas has to balance the economic needs and the effective use of resources. This study aims to analyze the suitability level of Samudra Indah Beach as a beach tourism object based on some parameters of the suitability of the tourist area and to analyze its carrying capacity. This study is descriptive using the Index of Tourism Suitability and Carrying Capacity which results in the values of suitability and carriying capacity of the tourism area. The parameters observed include depth, beach type, base substrate type, beach width, beach slope, current velocity, water brightness, land cover, hazardous biota, and freshwater availability calculating the maximum number of visitors accommodated in the area at a certain time without causing disturbance to nature and humans. The results showed that the Samudra Indah Beach area was included in the category of highly appropriate (S1) particularly for beach recreation and swimming. This beach can accommodate around 8,333 visitors/day.